Transient Retrovirus-Based CRISPR/Cas9 All-in-One Particles for Efficient, Targeted Gene Knockout - Yvonne Knopp; Franziska K. Geis; Dirk Heckl; Stefan Horn; Thomas Neumann; Johannes Kuehle; Janine Meyer; Boris Fehse; Christopher Baum; Michael Morgan; Johann Meyer; Axel Schambach; et al. (Elsevier, 2018)
The recently discovered CRISPR/Cas9 system is widely used in basic research and is a useful tool for disease modeling and gene editing therapies. However, long-term expression of DNA-modifying enzymes can be associated with cytotoxicity and is particularly unwanted in clinical gene editing strategies. Because current transient expression methods may still suffer from cytotoxicity and/or low efficiency, we developed non-integrating retrovirus-based CRISPR/Cas9 all-in-one particles for targeted gene knockout. By redirecting the gammaretroviral packaging machinery, we transiently delivered Streptococcus pyogenes Cas9 (SpCas9) mRNA and single-guide RNA transcripts into various (including primary) cell types. Spatiotemporal co-delivery of CRISPR/Cas9 components resulted in efficient disruption of a surrogate reporter gene, as well as functional knockout of endogenous human genes CXCR4 and TP53. Although acting in a hit-and-run fashion, knockout efficiencies of our transient particles corresponded to 52%-80% of those obtained from constitutively active integrating vectors. Stable SpCas9 overexpression at high doses in murine NIH3T3 cells caused a substantial G0/G1 arrest accompanied by reduced cell growth and metabolic activity, which was prevented by transient SpCas9 transfer. In summary, the non-integrating retrovirus-based vector particles introduced here allow efficient and dose-controlled delivery of CRISPR/Cas9 components into target cells. Keywords: CRISPR/Cas9 all-in-one particle, transient delivery, cytotoxicity, gammaretroviral MS2 chimera, targeted gene knockout, genome editing